UJI DAYA HAMBAT EKSTRAK BATANG BROTOWALI (Tinospora crispa (L) miers) TERHADAP BAKTERI Escherichia coli DAN Staphylococcus aureus DENGAN METODE DIFUSI CAKRAM - Radho Al Kausar; Muhammad Sahrul (Jurnal Analis Farmasi, 2022)
This study aimed to test the inhibitory power of brotowali stem extract (Tinospora crispa (L) Miers) against Escherichia coli and Staphylococcus aureus bacteria. The extraction method used was maceration with 96% ethanol solvent, the inhibition test was carried out using the disc diffusion method. The test was carried out with three repetitions with a concentration of 75%, 50%, and 25%. Then tested on Escherichia coli and Staphylococcus aureus with Nutrian agar media. Brotowali stem extract (Tinospora crispa (L) Miers) was found to be able to inhibit both bacteria. Brotowali stem extract (Tinospora crispa (L) Miers) was able to inhibit Escherichia coli bacteria, with inhibition zone diameters of 25% 19.36 mm, 50% 19.87 mm, and 75% 19.87. and stem extract of brotowali (Tinospora crispa (L) Miers) was able to inhibit Staphylococcus aureus bacteria, with inhibition zone diameters of 25%19.59 mm, 50% 19.85 mm, and 75% 20.01. Conclusion brotowali stem extract can inhibit bacterial Escherichia coli dan Staphylococcus growth.